Factors Determining the Successful Implementation of New Information Technology in a Professional Union - Solomon, Norman; Templer, Andrew (Relations industrielles / Industrial Relations, 1992)
The successful implementation of information technology in a teachers federation in a Canadian province is examined. At least 3 key factors seem to account for successful implementation: 1. the presence of an influential and energetic technology advocate, 2. the involvement of users in the implementation, and 3. a general ethos in the organization that encourages excellence in the services provided by staff but within a collegial framework. It is clear that the federation was successful in harmonizing the interests of employees and members. The appointment of an executive assistant was crucial in focusing attention on the technology issue. Building on the mission given to him by the elected officials, the executive assistant played a key role in gaining organizational commitment to new technology. Also important to success was the attention the federation paid to getting input from professional and non-professional staff about decisions concerning information technology.
Keywords: Automation; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Computer applications; Implementations; Information management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Unions